INHIBISI KOROSI BAJA SS-304 MENGGUNAKAN EKSTRAK TANAMAN PUTRI MALU - julita manuhutu (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2021)
Research has been conducted to determine the inhibition efficiency and steel corrosion rate of SS-304 in H2SO4 solvent using the leaves of Mimosa Pudica extract with the weight reduction method. The extract of Mimosa Pudica leaves was obtained through maceration extraction using methanol. Phytochemical test results showed that in Mimosa Pudica leaves extract contained flavonoids, alkaloids, tannins, terpenoids, and saponins. The results showed that inhibition efficiency increased with increasing inhibitor concentration, which means that the corrosion rate decreases. The optimum of inhibition efficiency obtained at a concentration of 2%, namely 87.81% with a corrosion rate of 6.21 mmy-1. The inhibition efficiency increases with increasing temperature, but not linear as shown at the curve, which means that the inhibitor layer on the steel surface was not stable at high temperatures, while the corrosion rate per year increases with increasing temperature. The optimum of inhibition efficiency obtained at 35oC, namely 93.26% with a corrosion rate of 6.81 mmy-1.